Intra- and inter-rater reliabilities of measurement of ultrasound imaging for muscle thickness and pennation angle of tibialis anterior muscle in stroke patients. Issue 5 (4th July 2017) - Cho, Ki Hun; Lee, Hwang Jae; Lee, Wan Hee
Abstract: Background: Dysfunction of skeletal muscle has been commonly reported in stroke patients. Objective: The purpose of this study was to investigate the intra- and inter-rater reliabilities of measurement of ultrasound imaging (USI) for pennation angle (PA) and muscle thickness (MT) of tibialis anterior muscle in stroke patients. Methods: Thirty-four stroke patients (19 men) participated in this study. USI was used for measurement of PA and MT of the tibialis anterior muscles at rest and during maximum voluntary contraction (MVC). Two examiners acquired images from all participants during two separate testing sessions, seven days apart. Intra-class correlation coefficients (ICCs), confidence interval (CI), standard error of measurement, minimal detectable change, and Bland–Altman plots were used for estimation of reliability. Results: In the intra-rater reliability between measures, for all variables (PA and MT of the paretic and non-paretic sides of tibialis anterior muscles at rest and during MVC), the ICCs ranged between 0.639 and 0.998 and the CI was within an acceptable range of 0.388–0.999. In inter-rater reliability between examiners for the two tests, for all variables, the ICCs ranged between 0.690 and 0.995 and the CI was within an acceptable range of 0.463–0.997. In addition, significant difference was observed between the paretic and non-paretic sides of the tibialis anterior muscle architecture ( p  < 0.05). Conclusion: These finding demonstrate that measurements of the tibialis anterior muscle using USI can be useful for clinical assessment in stroke patients. In addition, objective and quantitative measurements of tibialis anterior muscle using USI may provide appropriate management for the walking recovery of stroke patients.